Analisis Hukum Islam Terhadap Status Nasab Anak Akibat Married By Accident Dalam Film Dua Garis Biru - Hayatun Nufus; Musyaffa Amin Ash-Shabah; Suprihatin; Agus Supriyanto; Shabah, Musyaffa (Institut Agama Islam Negeri Metro, 2025)
Abtrack: This study aims to analyze Islamic law's perspective on the phenomenon of marriage by accident, as highlighted in the film